Midazolam exhibits antitumour and anti-inflammatory effects in a mouse model of pancreatic ductal adenocarcinoma. (April 2022) - Oshima, Yukino; Sano, Makoto; Kajiwara, Ichie; Ichimaru, Yoshimi; Itaya, Tomoaki; Kuramochi, Tomoya; Hayashi, Emiko; Kim, Jinsuk; Kitajima, Osamu; Masugi, Yohei; Masamune, Atsushi; Ijichi, Hideaki; et al.
Abstract: Background: Anaesthesia and perioperative management contribute to long-term outcomes of patients with cancer, including pancreatic ductal adenocarcinoma. We assessed the antitumour, anti-inflammatory, and analgesic effects of midazolam on LSL-Kras G12D/+ ;Trp53 flox/flox ;Pdx-1 cre/+ transgenic mice with pancreatic ductal adenocarcinoma. Methods: Six-week-old transgenic mice were administered midazolam 30 mg kg −1 day −1 p.o. ( n =13); midazolam 30 mg kg −1 day −1 with 1-(2-chlorophenyl)-N-methyl-N(1-methylpropyl)-3-isoquinoline carboxamide (PK11195) 3 mg kg −1 day −1 i.p., a peripheral benzodiazepine receptor antagonist ( n =10); or vehicle (water; n =14) until the humane endpoint. Cancer-associated pain was evaluated using hunching score and mouse grimace scale. Tumour stage and immuno-inflammatory status were determined histopathologically. Anti-proliferative and apoptotic potentials of midazolam were investigated using mouse pancreatic ductal adenocarcinoma cell lines. Results: Midazolam significantly inhibited tumour size and proliferative index of Ki-67 and cyclins in pancreatic ductal adenocarcinoma, which was blocked by administration of PK11195. Local myeloperoxidase + tumour-associated neutrophils, arginase-1 + M2-like tumour-associated macrophages, and CD11b + Ly-6G + polymorphonuclear myeloid-derived suppressor cells were reduced by midazolam, which was antagonised by administration of PK11195. Hunching and mouse grimace scale were improved by midazolam, whereas the scores increased with midazolam+PK11195 treatment. Plasma pro-inflammatory cytokines, such as interleukin-6 and CC chemokine ligand (CCL)2, CCL3, and CCL5, were reduced by midazolam, whereas these cytokines increased with PK11195. Midazolam inhibited pancreatic ductal adenocarcinoma proliferation through downregulation of cyclins and cyclin-dependent kinases and induced apoptosis in vitro . Conclusions: These results suggest that midazolam inhibits pancreatic ductal adenocarcinoma proliferation and local infiltration of tumour-associated neutrophils, tumour-associated macrophages, and polymorphonuclear myeloid-derived suppressor cells, thereby inhibiting pancreatic ductal adenocarcinoma progression.